Validasi dan Respon Siswa terhadap Komik Digital Bioteknologi Berbasis Potensi Lokal Kalimantan Barat - Fitriani Fitriani; Hanum Mukti Rahayu; Anandita Eka Setiadi; Helda Susanti (SAP (Susunan Artikel Pendidikan), 2023)
The learning media in SMA Muhammadiyah 1 Pontianak quite varied, but they are limited to print media that do not contain local potential. One media that expected to be used by students of SMA Muhammadiyah 1 Pontianak in learning Biology is digital comics. The purpose of this study is to produce digital comic learning media based on the local potential of West Kalimantan which is valid and to get a positive response from students. This research was carried out in the even semester of the 2021/2022 academic year using Research and Development with a modified 4D model, namely, Define, Design and Develop without Dissemination. The data collection technique was a validation questionnaire filled in by 9 validators on aspects of media, material and language. Student responses were measured using a questionnaire on small-scale trials and large-scale trials. The results showed that the developed digital comic media obtained very valid scores on the media aspect (92.38%) and language aspects (82.42%), while on the material aspect it obtained a valid value (79.58%). Students gave very positive responses in small-scale trials (96%) and large-scale trials (99%). It was concluded that the media developed are valid and acknowledged very positive responses from students.